ANALISIS KEMAMPUAN BEPIKIR KRITIS MATEMATIK SISWA SMP DI KABUPATEN BANDUNG BARAT - Nina Lestari; Riki Andriansyah; Dinar Nur Azizah; Sopian Lukman; Wahyu Hidayat (IKIP Siliwangi, 2018)
The ability to think critically is one of the highest levels of ability. Developing critical thinking skills in students is still considered important to be improved in schools so that students are able and accustomed to facing various problems around it. This study aims to analyze the critical thinking skills of junior high school students who are in excellent classes and regular classes. This research was conducted in Bandung Barat. In this study students are given a test in the form of questions with critical thinking skills, the problem is used to compare between the superior class and ordinary class. Assessment of the problem using several factors of critical ability include 1) students can not understand the problem correctly, 2) students rush in doing the problem, 3) the students cannot choose the problem-solving strategy correctly and 4) the students work on the problem systematically. Then the matter of critical thinking skills of mathematics is analyzed using quasi-experimental research method to analyze students' critical thinking ability that influence learning result. This study shows the differences in critical thinking ability of junior high school students who are in excellent class and ordinary class. This study shows that superior classes are better in mathematical critical thinking ability than a regular class. The results of this study can add knowledge about critical thinking mathematics junior high school students who are in the class and ordinary class and used to facilitate for educational practitioners in the development of critical mathematical thinking skills.